(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
In this work we studied the synthesis of phosphonate triethanolamine borate (PTEAB-1). Take 10.8 g of triethanolamine borate substance (0.6 mmol) and dissolve in 50 ml of distilled water, place in a 100 ml two-neck round-bottom flask, select phosphorous acid (4.92 g or 0.6 mmol) and dissolve in 2-3 ml of distilled water to prepare the solution. In the next step, a 37% HCHO solution (0.726 g or 8.94 mmol) was slowly added to this heated solution under an inert nitrogen atmosphere and the process was carried out at 115 °C for 24 hours. Fourier transform infrared (FTIR) spectra were recorded on an IRAffinity-1S FTIR spectrometer (Shimadzu, Japan).